The world at war the landmark oral history from the previously unpublished archives - Holmes, Richard 1946- (Ebury, 2007)
The World at War is the definitive television work on the Second World War. It set out to tell the story of the war through the testimony of key participants - from civilians to ordinary soldiers, from statesmen to generals. First broadcast in 1973, the result was a unique and irreplaceable record since many of the eyewitnesses captured on film did not have long to live. The programme's producers committed hundreds of interview-hours to tape in its creation, but only a fraction of that material made it to the final cut. For more than 30 years the interviews have never been allowed to be published - until now. Highly respected historian and bestselling author Richard Holmes has skilfully woven this valuable original material into a compelling narrative, creating a truly phenomenal oral history of the Second World War. - Publisher.